DINAMIKA PENGARUSUTAMAAN MODERASI BERAGAMA DALAM PERKEMBANGAN MASYARAKAT DIGITAL - Mahyudin; Muhammad Alhada Fuadilah Habib; Sulvinajayanti (Prodi Sosiologi Agama, 2022)
This article was written as a note in responding to the mainstreaming of religious moderation in Indonesia by examining the dynamics and challenges in the midst of social change in the digital era. This research used literature study. The findings of this research showed that religious expressions shown by adherents of religions cannot be avoided from the tendency to come into contact with digital technology. Religious people, in turn, come into contact with contradictory of digital cultures that give rise to fragmentation and contestation. Moderation campaigns in the digital space to sow messages of peace between religions are now faced with the phenomenon of religious disruption, especially in the digital space. This phenomenon clearly has social implications for social harmony because the scale does not only occur at the internal level of religious communities but also between religious communities. This study recommends revitalizing digital literacy the idea of religious moderation as a process of forming awareness of religious moderation in Indonesian society in the era of digital society.